Epidemiology of leisure-time physical activity: a population-based study in southern Brazil - Juvenal Soares Dias-; Pedro Curi Hallal; Jonathan Charles Kingdon Wells; Tiago Daltoé; Sandra Costa Fuchs; Ana Maria Baptista Menezes; Maria Teresa Anselmo Olinto
We aimed to measure the prevalence of physical inactivity (PI) during leisure time and to identify variables associated with it in a southern Brazilian adult population. A population-based cross-sectional study was carried out, covering a multiple-stage sample of 1,968 subjects aged 20-69 years. Weekly participation in leisure-time physical activity was addressed. For each activity, energy expenditure was calculated using data on duration, metabolic equivalent, and body weight. Energy expenditures of individual activities were summed to give a weekly total. PI was defined as fewer than 1,000 kilocalories per week. The prevalence of PI was 80.7% (95%CI: 78.9-82.4). After adjusted analyses, the following variables were positively associated with the outcome: female gender, age, living with a partner, and smoking. Schooling and economic status were inversely associated with PI. Chronically undernourished individuals were significantly more likely to be inactive. We found no differences according to skin color or alcohol consumption. In conclusion, the prevalence of PI in this adult population was higher than in populations from developed countries, but the associated variables were similar.